Synthesis of poly(methyl methacrylate) and block copolymers by semi-batch nitroxide mediated polymerization. Issue 45 (27th October 2016) - Ballard, N.; Simula, A.; Aguirre, M.; Leiza, J. R.; van Es, S.; Asua, J. M.
Abstract : The limits of control of the molecular weight and polymer structure in the semi-batch solution polymerization of methyl methacrylate by NMP are explored. Abstract : In order to successfully implement the commercial synthesis of polymers by using reversible deactivation radical polymerization (RDRP) techniques in solution, semi-batch processes should be developed. However, the low monomer concentrations involved present a challenge for RDRPs. This is especially the case in the nitroxide mediated polymerization of methacrylates where, historically, even in batch control over the polymerization has been difficult. Here, we show that the alkoxyamine, 3-(((2-cyanopropan-2-yl)oxy)(cyclohexyl)amino)-2, 2-dimethyl-3-phenylpropanenitrile, which was recently shown to successfully control the polymerization of methyl methacrylate and styrene, can also be used to control the polymerization of methacrylates under semi-batch conditions. High instantaneous conversions, whilst maintaining the polymer end groups are observed and the limits of control over the polymerization and the potential to synthesize block copolymers under semi-batch conditions are explored.